Parents’ Participation in Strengthening FAST Character through Learning From Home program - Paksi, Hendrik Pandu (International Conference on Elementary Education, 2022)
Character education for elementary school students was initially implemented through learning at school, extracurricular activities, school culture and community participation. However, when the world was hit by Covid-19 outbreak and became a pandemic, learning activities in school were stopped. Automatically, character education programs in school also stopped. In such conditions, parents’ participation is highly needed in character strengthening programs through learning from home programs. This research was using quantitative descriptive methods by observing and distributing questionnaires to 40 respondents, namely parents of students who participated in the program. The characters targeted by this program are FAST characters (Fathonah, Amanah, Shidiq and Tabligh). Results showed that 65% of respondents admitted that it was difficult to run this program because there are no manuals, while 32% of respondents had their own designed guidelines. As many as 90% of respondents were able to run the program according to the expected target while 10% of respondents had not reached the target. Meanwhile, 98% of respondents wish that this program can continue even after learning in schools has been recovered, while 2% of respondents would leave the affairs of childrens’ education to schools. Thus, it can be concluded that with parents’ participation, the character education program was successfully carried out through a learning from home program.